CGIAR Excellence in Agronomy Initiative - CGIAR Excellence in Agronomy Initiative (CGIAR Excellence in Agronomy Initiative, 2024)
This Initiative aims to deliver an increase in productivity and quality per unit of input (agronomic gain) for millions of smallholder farming households in prioritized farming systems by 2030, with an emphasis on women and young farmers, showing a measurable impact on food and nutrition security, income, resource use, soil health, climate resilience and climate change mitigation.